2010
DOI: 10.1107/s1744309110004318
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of perdeuterated diisopropyl fluorophosphatase (DFPase): perdeuteration of proteins for neutron diffraction

Abstract: PDB Reference: perdeuterated diisopropyl fluorophosphatase, 3kgg.The signal-to-noise ratio is one of the limiting factors in neutron macromolecular crystallography. Protein perdeuteration, which replaces all H atoms with deuterium, is a method of improving the signal-to-noise ratio of neutron crystallography experiments by reducing the incoherent scattering of the hydrogen isotope. Detailed analyses of perdeuterated and hydrogenated structures are necessary in order to evaluate the utility of perdeuterated cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It is important to ensure that perdeuteration does not affect the overall structure of the protein. Although X-ray structures of perdeuterated proteins generally show no significant differences in the structures compared with nondeuterated proteins [14,26,38,39,46,47], Chatake and coworkers [48] showed there were differences in dissimilatory sulfite reductase D crystals soaked with various deuterium concentrations, although these did not translate to major structural differences. Liu and coworkers [25] did find that a catalytic residue was displaced in the deuterated structure, and as a consequence a water molecule, which is suspected to play a role in the catalysis of haloalkane dehalogenase, was not present in the perdeuterated structure, indicating that it is important to determine that perdeuteration does not affect the protein structure.…”
Section: Discussionmentioning
confidence: 94%
“…It is important to ensure that perdeuteration does not affect the overall structure of the protein. Although X-ray structures of perdeuterated proteins generally show no significant differences in the structures compared with nondeuterated proteins [14,26,38,39,46,47], Chatake and coworkers [48] showed there were differences in dissimilatory sulfite reductase D crystals soaked with various deuterium concentrations, although these did not translate to major structural differences. Liu and coworkers [25] did find that a catalytic residue was displaced in the deuterated structure, and as a consequence a water molecule, which is suspected to play a role in the catalysis of haloalkane dehalogenase, was not present in the perdeuterated structure, indicating that it is important to determine that perdeuteration does not affect the protein structure.…”
Section: Discussionmentioning
confidence: 94%
“…In the course of the crystallographic refinement, a strong electron density was found inside the β-propeller structure in both mouse and human SMP30/GNL. Earlier structure analysis of relevant molecules [11], [13][15] suggested that the strong density represents a divalent metal ion. The ICP-MS analysis suggested that the divalent metal ion bound to SMP30/GNL molecules in the crystal showed heterogeneity; the SMP30/GNL molecules bound Mn 2+ , Zn 2+ , Mg 2+ , or Ca 2+ in the crystal ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of mouse SMP30/GNL was compared with other related enzymes, human SMP30/GNL [11], DFPase [13], Drp35 [14], PON [15], and a putative GNL (PDB ID: 3E5Z) in PDB. The overall folds of these proteins were essentially the same, i.e., they adopted a six-bladed β-propeller structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations